2017
DOI: 10.1534/g3.117.042655
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Mitochondrial Genome To Enhance Cattle Embryo Development

Abstract: The mixing of mitochondrial DNA (mtDNA) from the donor cell and the recipient oocyte in embryos and offspring derived from somatic cell nuclear transfer (SCNT) compromises genetic integrity and affects embryo development. We set out to generate SCNT embryos that inherited their mtDNA from the recipient oocyte only, as is the case following natural conception. While SCNT blastocysts produced from Holstein (Bos taurus) fibroblasts were depleted of their mtDNA, and oocytes derived from Angus (Bos taurus) cattle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 85 publications
(102 reference statements)
1
29
0
Order By: Relevance
“…Our previous report showed that depleting mtDNA from donor cells prior to SCNT can prevent the transmission of donor cell mtDNA to the embryo as these embryos harboured only oocyte mtDNA. Furthermore, the gene expression patterns of embryos produced from depleted cells were different to those of nondepleted cells 35 . Collectively, this resulted in an improvement to SCNT.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Our previous report showed that depleting mtDNA from donor cells prior to SCNT can prevent the transmission of donor cell mtDNA to the embryo as these embryos harboured only oocyte mtDNA. Furthermore, the gene expression patterns of embryos produced from depleted cells were different to those of nondepleted cells 35 . Collectively, this resulted in an improvement to SCNT.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, we compared expression patterns of miNT blastocysts derived from depleted cells cultured in the absence and presence of TSA to SCNT blastocysts derived from depleted cells cultured in the presence of TSA, which we assumed to be the gold standard, as we have previously demonstrated for SCNT embryos 35 . For the comparison between miNT blastocysts derived from depleted cells cultured in the absence of TSA and SCNT blastocysts derived from depleted cells cultured in the presence of TSA, 454 out of the 894 DEGs were upregulated (FDR < 0.05, Supplementary File 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In cattle, in an attempt to mimic the natural conception process, mitochondrial DNA (mtDNA) was depleted from donor cells, and the effects of TSA during embryo culture were evaluated. TSA treatment improved blastocyst formation of SCNT embryos originating from mtDNA-depleted donor cells to rates observed for embryos derived from nondepleted cells (Srirattana & John, 2017). However, supplementation with mtDNA in depleted donor cells enhanced reprogramming of SCNT embryos when compared to the co-treatment with TSA or TSA alone (Srirattana & John, 2018).…”
Section: Strategies For Epigenetic Regulation Of Scnt-derived Embryosmentioning
confidence: 86%